NSV11749, an elder sibling of the born-again stars V605Aql and V4334Sgr? - Miller Bertolami, Marcelo Miguel (2011)
We argue that NSV11749, an eruption observed in the early twentieth century, was a rare event known as "very late thermal pulse" (VLTP). To support our argument we compare the light curve of NSV11749 with those of the two bona fide VLTP objects known to date, V4334Sgr and V605Aql, and with those predicted by state-of-the-art stellar evolution models. Next, we explore the INT Photometric H-Alpha Survey (IPHAS) and Two Micron All Sky Survey (2MASS) catalogs for possible counterparts of the eruption. Our analysis shows that the VLTP scenario outperforms all other proposed scenarios as an explanation of NSV11749. We identify an IPHAS/2MASS source at the eruption location of NSV11749. The derived colors suggest that the object is not enshrouded in a thick dust shell as V605Aql and V4334Sgr. Also, the absence of an apparent planetary nebula at the eruption location suggests differences with known VLTP objects which might be linked to the intensity of the eruption and the mass of the object. Further exploration of this source and scenario seems desirable. If NSV11749 was a born-again star, it would be the third event of its kind to have been observed and will strongly help us to increase our understanding of the later stages of stellar evolution and violent reactive convective burning.